Pengolahan Limbah Cair Rumah Sakit dengan Metode Lahan Basah Buatan (Constructed Wetland) dan Tanaman Air Typha latifolia - Hasan, Amrul; Suprapti, Suryani Catur (Poltekkes Kemenkes Tanjung Karang, 2021)
Utilization of the aquatic plant Typha latifolia, in the treatment of hospital wastewater with the method of an artificial wetland system (constructed wetland), is expected to be able to treat the liquid waste of health care facilities. This study aims to determine the ability of the aquatic plant Typha latifolia in degrading the parameters contained in the wastewater of health facilities using the Artificial Wetland Method. Quasi-experimental research design. The measurement of liquid waste parameters (BOD, COD, TSS, Fatty Oil, and Ammonia) is carried out by taking samples at the inlet and outlet of each pot, then analyzed in the laboratory. The study reported an average influent BOD level of 66.2mg/L, an average effluent in a circular cross-sectional pot increased by 99.6mg/L, an influent COD level of 190.8mg/L, an effluent in a rectangular pot four decreased by an average of 31.6mg/L, the influent TSS parameter was 106mg/L, the average effluent in a circular cross-sectional pot was 283.6mg/L, the influent Oil & Fat parameter averaged 1.2mg/L, average effluent 1.2mg/L, ammonia influent parameter 12mg/L, effluent 2.62mg/L. The rectangular cross-section has a good ability compared to other cross-sections in reducing hospital waste, namely; BOD=64%, COD=40%, TSS=48%, Ammonia=67%, Oil and Fat parameters did not decrease because the influent parameter levels were already below the Liquid Waste quality standard. The researcher concluded that the rectangular cross-sectional pot planted with Typha latifolia could reduce the wastewater parameters better than other cross-sectional types.Â